The Correlation of Pemogan Community Knowledge about Usada Taru Pramana with the Behaviour of Utilization and Conservation of Herbal Medicine - Ni Putu Udayana Antari; I Putu Tangkas Suwantara; Erna Cahyaningsih (Faculty of Pharmacy, Universitas Gadjah Mada, 2017)
Usada Taru Pramana is a record of hundreds medicinal plants. Researcher is interested to know the knowledge level of Pemogan Villager about Usada Taru Pramana and its influence on the utilization behavior and conservation of herbal medicine. Data were collected using a valid and reliable structured questionnaire with a cross-sectional survey design. According to Spearman's test result from total 150 samples, Pemogan Villager knowledge about Usada Taru Pramana is not correlated with the utilization behavior and conservation of herbal medicine (P value=0,280 and r=0,089). There were no significant differences between the both variables with respondents' education level, age and gender. The results showed that the factor which influenced the studied variables is very complex. There were